Teaching veterinary surgical skills: Comparison of massed versus spaced instruction. Issue 7 (25th August 2022) - Banse, Heidi E.; Baker, Rose E.; Domaracki, Cullen; McCauley, Charles; Duhon, Brandy; Grandt, Beth; Jackson, Kate; Spangler, Dawn M.; Hunt, Julie A.
Abstract: Objective: To determine the effect of massed instruction (MI) versus spaced instruction (SI) of veterinary surgical skills on students' cognitive load and skill retention. Study design: Prospective randomized cohort study Study population: First‐year veterinary students from Louisiana State University (LSU; n = 47) and Lincoln Memorial University (LMU; n = 101). Methods: Students were randomized to MI (two skills in a single session of twice the duration) or SI (one skill per session on two consecutive days). Instructors, instructional ratio, and total educational time was equivalent. Following instruction, students completed a cognitive load questionnaire and underwent a structured assessment immediately after (LMU only), 1 day after, and 3‐4 weeks after learning the second skill. Students completed two supervised practice sessions one and 2 weeks after the initial laboratory session(s). Results: Overall cognitive load did not differ between groups ( p > .05), although LMUs MI group reported higher physical and time demands, effort, and frustration. At initial assessment, SI students scored higher than MI students for the first skill at both LSU (mean checklist score = 27.7 vs. mean = 24; p = .004) and LMU (mean global rating score = 4.76 vs. mean = 4.55; p = .029). Differences between groups were no longer evident by 3–4 weeks after instruction. Conclusion: SI may lead to improved immediate performance; however, supervised practice was sufficient to overcome the initial disparity. Clinical significance: SI may be beneficial for initial skill performance. However, SI and MI students had similar performance after 3 weeks, suggesting the more convenient curricular design of MI may be sufficient as long as practice sessions are incorporated.